Effects of adenine sulfate and sugar type on the growth and development of shoots induction of papaya callus in vitro - Intanu, Adisak; Chidburee, Piengpim; Chidburee, Aphichat (Health Science, Science and Technology Reviews, 2023)
The aim of this research work was to study the different concentrations of adenine sulfate (Ads) and sugar types on papaya’s growth and development of shoot-induced callus explants. There were two experiments. The first experiment studied different Ads concentrations: no fill (control), 25, 50 and 75 mg/l. Ads was added to the Murashige and Skoog (MS) medium. Data was recorded for four weeks after culture. The results showed that the callus explants cultured on MS medium added with 50 mg/l Ads have the highest number of new shoots per explant (7.00 shoots per explant) and shoot length (5.15 mm). The second experiment examined two types of sugars, sucrose and glucose, compared with no sugar added (control). The result showed that the percentage of new shoots and the number of new shoots per explant were not different when cultured on both sugar-added media but were different from no sugar added (control). The callus explant cultured on 3% glucose added has an increased number of new shoots per explant.